Alveolar Bone Marrow Gli1+ Stem Cells Support Implant Osseointegration. (January 2022) - Yi, Y.; Stenberg, W.; Luo, W.; Feng, J.Q.; Zhao, H.
Osseointegration is the key issue for implant success. The in vivo properties of cell populations driving the osseointegration process have remained largely unknown. In the current study, using tissue clearing–based 3-dimensional imaging and transgenic mouse model-based lineage tracing methods, we identified Gli1+ cells within alveolar bone marrow and their progeny as the cell population participating in extraction socket healing and implant osseointegration. These Gli1 + cells are surrounding blood vessels and do not express lineage differentiation markers. After tooth extraction and delayed placement of a dental implant, Gli1 + cells were activated into proliferation, and their descendants contributed significantly to new bone formation. Ablation of Gli1 + cells severely compromised the healing and osseointegration processes. Blockage of canonical Wnt signaling resulted in impaired recruitment of Gli1 + cells and compromised bone healing surrounding implants. Collectively, these findings demonstrate that Gli1 + cells surrounding alveolar bone marrow vasculature are stem cells supporting dental implant osseointegration. Canonical Wnt signal plays critical roles in regulating Gli1 + stem cells.